2017
DOI: 10.1126/scitranslmed.aaf6295
|View full text |Cite
|
Sign up to set email alerts
|

Complement C3 deficiency protects against neurodegeneration in aged plaque-rich APP/PS1 mice

Abstract: The complement cascade not only is an innate immune response that enables removal of pathogens but also plays an important role in microglia-mediated synaptic refinement during brain development. Complement C3 is elevated in Alzheimer's disease (AD), colocalizing with neuritic plaques, and appears to contribute to clearance of Aβ by microglia in the brain. Previously, we reported that C3-deficient C57BL/6 mice were protected against age-related and region-specific loss of hippocampal synapses and cognitive dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
341
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 458 publications
(411 citation statements)
references
References 71 publications
22
341
1
Order By: Relevance
“…D, E In the probe trial 24 h after the last training day, the time mice spent in the target quadrant (TQ) was different from chance in all groups except for APP/PS1-Stat3WT mice (P < 0.05, one-tailed one-sample t-test). Moreover, we also found that C3d, a characteristic product of "A1" astrocytes (Liddelow et al, 2017) that contributes to AD pathology (Shi et al, 2017), is strongly reduced by astrocyte Stat3 deletion. Importantly, the effects on cognition and network function were recapitulated by chronic treatment with a systemic Stat3 inhibitor.…”
Section: Discussionsupporting
confidence: 52%
“…D, E In the probe trial 24 h after the last training day, the time mice spent in the target quadrant (TQ) was different from chance in all groups except for APP/PS1-Stat3WT mice (P < 0.05, one-tailed one-sample t-test). Moreover, we also found that C3d, a characteristic product of "A1" astrocytes (Liddelow et al, 2017) that contributes to AD pathology (Shi et al, 2017), is strongly reduced by astrocyte Stat3 deletion. Importantly, the effects on cognition and network function were recapitulated by chronic treatment with a systemic Stat3 inhibitor.…”
Section: Discussionsupporting
confidence: 52%
“…These complement C3-knockout AD mice performed better on learning and memory tests despite having more cerebral Aβ deposition. The reduced level of pro-inflammatory markers in these AD mice highlights the important role of inflammation in AD and suggests that targeting the inflammatory pathway could be highly beneficial in treating this disease 59 . Consistent with this finding, our group has shown that reducing neuroinflammation by depleting FXII improves the cognitive function of AD mice 25 .…”
Section: Discussionmentioning
confidence: 97%
“…Recently, complement has been linked to age‐related neurodegeneration. Complement C3‐deficient mice failed to display an age‐related hippocampal decline in the typical aging process (Shi et al, ) and displayed less neurodegeneration in aged AD model mice (Shi et al, ). Thus, decreased loss of neurons in TREM2 KO mice possibly might be related to the reduced complement expression.…”
Section: Discussionmentioning
confidence: 99%